When no color pattern is available: Application of double observer methods to estimate population size of the Alpine salamander - Antonio Romano (Taylor & Francis Group, 2021)
Monitoring wild populations is an essential tool to assess the conservation status and the ecological requirements of a species. Capture–mark–recapture (CMR), based on individual recognition, is the most commonly used and most effective technique. However, in cases of species with no individual color pattern, tracing the encounter history of individuals without invasive marking methods is impossible. In this study we aimed to (1) estimate population abundance and density using a less effort-intensive and nonstressful technique, (2) test a long-term monitoring protocol, and (3) assess the fine-scale ecological requirements of a black-colored amphibian, Salamandra atra, in the Italian Alps. For three populations we applied an N-mixture model on data collected using a dependent double-observer approach. To understand ecological requirements, we assessed the relative importance of a set of environmental and topographical variables. The double-observer approach was a cost-effective technique that provided reliable demographic estimates of population density. Our results suggest that the most important fine-scale ecological variables positively associated with salamander abundance were canopy cover and terrain ruggedness, which are strictly related to shelter availability and soil moisture.